Implementasi Kurikulum Merdeka di Lembaga Bimbingan Belajar Luar Sekolah: Tinjauan Naratif Antara Adaptasi Administratif dan Praktik Substantif - Arditya Prayogi; Silmi Afifah; Trinindita Nayla Nabilla; Sabila Faiza Al Izzati Amin; Tri Purnama Sari; Moh. Syaifuddin; Riki Nasrullah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
The implementation of the Independent Curriculum has been studied primarily within the context of formal education, while discussion of non-formal tutoring institutions remains relatively limited. Tutoring institutions, however, are part of non-formal education and are also impacted by changes in curriculum orientation, particularly in aspects of learning flexibility, differentiation, diagnostic assessment, and learner-centered learning. This article aims to narratively examine how the implementation of the Independent Curriculum in non-formal tutoring institutions is positioned in the literature, particularly within the spectrum between administrative adaptation and substantive practice. This article uses a narrative literature review method, using data sources in the form of journal articles, proceedings, scientific books, and policy documents traced through various data indexing platforms. The results of the study indicate that the implementation of the Independent Curriculum in tutoring institutions tends to be present at the administrative level through the use of terminology, tools, and claims of curriculum adjustment, but has not been fully accompanied by in-depth pedagogical changes. This condition is influenced by a focus on quick results, time constraints, demands of the education market, and the absence of contextual implementation guidelines. This article emphasizes the need for implementation models and evaluation indicators that are more appropriate to the characteristics of non-formal education.